Pengaruh Relaksasi Autogenik terhadap Penurunan Tekanan Darah pada Klien Hipertensi di Wilayah Kerja Puskesmas 23 Ilir Palembang Tahun 2015 - Mardiono, Sasono (Jurusan Keperawatan FIKES UNSOED, 2016)
Hypertension is an increasing arterial blood pressure which is abnormally persistent when systolic blood pressure equal to or greater than 140 mmHg and diastolic equal to or greater than 90 mmHg. Medical management of clients with hypertension were not only by pharmacological methods solely, but also by non-pharmacological treatments. One non pharmacology therapy technique, that can lowers blood pressure, was autogenic relaxation. Relaxation is autogenic relaxation specific which implies that you have the ability to control body functions, such as heart rate, blood pressure and blood flow. The design of this research was quasi experiment with the approach pre and post test only design. The purpose of this study was to determine the effect of autogenic relaxation to decrease blood pressure in hypertensive clients in the region of Palembang Ilir 23 health centers in 2015. The sample in this study was accidental sampling. Autogenic relaxation on the respondent performed three times and measured blood pressure as much as six times. Statistical test used T Dependent. The result of this research are there were some effects of autogenic relaxation namely the decreasing of blood pressure (p value = 0.000). It was concluded that there was effect of autogenic relaxation on decreasing blood pressure of hypertension clients. Based on the results of this study are expected to autogenic relaxation techniques can be applied to lower blood pressure in hypertensive clients. And to disseminate the research results to the clients of hypertension, so people know the benefits of hypertension autogenic relaxation in lowering blood pressure.